Optimization of Polyphenols Release from Highland Barley Bran by Solid-State Fermentation and Antioxidant Activity Characterization - Qianfang Zhang; Min Li; Zhe Cheng; Jingyan Meng; Yunlong Li (Fermentation, 2024)
Response surface tests were used to determine the optimal conditions for Bacillus subtilis solid-state fermentation of highland barley bran. The polyphenol composition and antioxidant activity of the fermented bran were also assessed. The results showed that the optimal fermentation conditions for highland barley bran were 10% inoculum, a liquid–feed ratio of 1.80, a fermentation temperature of 30 °C, and a fermentation time of 93.5 h. Under these conditions, the polyphenol content of highland barley bran was 12.43 mg/g. After fermentation, the ferulic acid content of the bran decreased, catechol and gallic acid contents increased significantly, and catechins shifted from the bound state to the free state. In addition, solid-state fermentation improved the antioxidant capacity of highland barley bran, and the DPPH• radical scavenging rate, Fe ion-reducing capacity, and hydroxyl radical scavenging rate of highland barley bran increased after fermentation.